Design of New Electrode Interface to Improve Transport of Atmospheric Pressure Ions into a Mass Spectrometer - Francis Beaudry; Robert B. Moore (E-Journal of Chemistry)
An intermediate electrode was developed to improve the transfer of ions in atmospheric pressure from a first location, the ion source, to a second location, the mass spectrometer. The new apparatus increase the efficiency of mass analysis of molecular constituents of liquids, including trace analysis of chemical entities, in which an electrospray (ES) or IonSpray™ (IS) technique is used to produce electrically charged droplets which divide and evaporate to form gaseous ions of the molecular constituents. The gas phase ions are transported to the mass spectrometer by an electric field generated by a new electrode design that separates the two fundamental functions of an electrospray or an IonSpray™, which are the nebulization of charged droplets and the transport of ions into the mass analyzer. The results suggest that the new apparatus provide a gain in signal intensity up to 10 compared with the commercial product. A significant improvement in ion transport results in higher precision and accuracy and/or reduction of the amount of material needed for analysis.